Real-world efficacy and safety of dupilumab in children with atopic dermatitis under 6 years of age: a retrospective multicentric study - Rob, Filip; Pinkova, Blanka; Sokolova, Kristyna; Kopuleta, Jana; Jiraskova Zakostelska, Zuzana; Cadova, Jana (The Journal of dermatological treatment, 2025)
In this multicentric real-world observational retrospective study, we evaluated the efficacy and safety of dupilumab for atopic dermatitis in children <6 years of age who underwent a minimum of 16 weeks of therapy. The analysis focused on EASI (Eczema Area and Severity Index), CDLQI (Children's Dermatology Life Quality Index), and Itch NRS (Numeric Rating Scale) changes from baseline to 4, 16, 24, 48, 72, and 96 weeks of follow-up (when available). Overall 24 children were included, with a mean age of 4.4 years. The baseline mean EASI among these patients was 26.7 (range 11.2-42.5). Since week 16 of therapy, all patients achieved and sustained at least 50% (EASI-50) atopic dermatitis improvement from baseline for the remainder of the follow-up period. At week 16, the mean EASI was 4.6 (0.8-13.1), EASI-75 reached 75% and EASI-90 38% of the patients. Within the initial 16 weeks of dupilumab treatment, 50% of patients experienced at least one adverse event, none of which were deemed severe. Conjunctivitis was among the most common adverse events (8.3%). In conclusion, dupilumab exhibited favorable tolerability, efficacy, and safety in children diagnosed with atopic dermatitis who were below the age of 6.
Keywords: stupeň závažnosti nemoci; children; Atopic dermatitis; Retrospective Studies; kojenec; dermatologické látky; lidé; safety; výsledek terapie; mužské pohlaví; Infant; kvalita života; Dermatitis, Atopic; biologics; Child, Preschool; efficacy; ženské pohlaví; retrospektivní studie; předškolní dítě; Humans; Antibodies, Monoclonal, Humanized; Dermatologic Agents; dupilumab; atopická dermatitida; Female; Quality of Life; Severity of Illness Index; Treatment Outcome; humanizované monoklonální protilátky; Male